Vascular disturbances in primary aldosteronism: clinical evidence - Widimsky, J; Strauch, B; Petrák, O; Rosa, J; Somloova, Z; Zelinka, T; Holaj, R (Kidney & blood pressure research, 2012)
Primary aldosteronism (PA) is a common form of arterial hypertension with a high prevalence of cardiovascular complications. In patients with PA, complex mechanisms may lead to functional and/or structural abnormalities of the blood vessel wall. Clinical evidence indicates that patients with PA may have immune cell activation, increased oxidative stress, impaired endothelial function and vascular remodeling. Activation of fibroproliferation has been found in resistant arteries of patients with PA. Subjects with PA compared to essential hypertensives with similar blood pressure levels have increased intima-media thickness and arterial stiffness as measured by pulse wave velocity. These functional and morphological changes can be modified by an increased sodium intake. Vascular remodeling in PA may indicate a poor response to specific therapy with lower probability of cure and/or normalization of blood pressure. Early diagnosis of PA before blood vessel wall disturbances develop is of utmost importance.
Keywords: krevní tlak; rychlost toku krve; Animals; cévní rezistence; Blood Flow Velocity; lidé; hypertenze; nemoci cév; zvířata; Hyperaldosteronism; Hypertension; Vascular Resistance; hyperaldosteronismus; Blood Pressure; Vascular Diseases; Humans